Pediatric Vitamin D Status: Age, Gender, and Seasonal Determinants in a Comprehensive Retrospective Cohort - Dündar, Ahmet; Çetik Yıldız, Songül; Irmak, Halit (The European Research Journal, 2026)
Objective: Vitamin D plays a critical role in bone health, immune function, and overall growth and development in children. So, the study aimed to determine serum vitamin D levels in a large sample, examine their relationship to age groups, gender, seasonal and monthly, and identify risk groups by demonstrating the prevalence of vitamin D deficiency in the pediatric age group. Methods: A retrospective study was conducted using serum vitamin D level data from pediatric patients presenting to the Pediatrics Outpatient Clinic. Children were divided into four age groups based on developmental stages: 1-4, 5-8, 9-12, and 13-17 years. Vitamin D levels were categorized as severe deficiency, deficiency, insufficiency, and normal. The data were analyzed for age, gender, seasonality, and monthly distribution, and the relationships between these variables were evaluated using comprehensive statistical methods. Results: Only 6.5% of the average vitamin D levels were found to be normal. Deficiency, insufficiency, or severe deficiency was detected in 93.5%. A weak but significant negative correlation was observed between age and vitamin D levels. While levels were similar between genders, severe deficiency was higher in females. The highest values were observed in summer and the lowest in winter, with July-September being the peak and January-February the trough. Conclusion: Our study revealed that vitamin D deficiency is common in children and a critical public health problem. Decreasing levels with age, seasonal cycles, and gender differences indicate that the risk becomes more pronounced. These findings highlight the need for supplementation plans and awareness-raising strategies, particularly during winter and spring.